Adherence status of HIV infected children at ART centre of South India - Nayak, Narayan V.; Prayag, Abhishek (International Journal of Contemporary Pediatrics, 2018)
Background: Adherence to antiretroviral therapy (ART) is a principal determinant of virologic suppression. A variety of factors: including formulation of medicine, dose frequencing, drug toxicities, child’s age, as well as psychosocial, behavioral, and sociodemographic characteristics of children and caregivers have been associated with nonadherence. Still no consistent predictors of either good or poor adherence in children have been consistently identified. Methods: Data was collected from the ART Centre. Record based data from the year 2008 to 2018 April of pediatric age group i.e. from 0-18 years. All the cases registered at the center whose data were available were included for the study. Adherence was assessed calculating the average monthly consumption of ARV assessed by pill count as per NACO guidelines. Results: At the ART Centre, 139 (73.5%) were on treatment i.e. 75.7% of boys registered and 70.9% of registered girls. Average monthly adherence and treatment interruptions among the 73 children alive on ART, majority i.e. 90.4% were on good adherence with 8.2% on less than 80% adherence. Conclusions: Overall a good adherence indicates efficient functioning of the programme and determined efforts from the ART Centre.